PENGARUH SISTEM PEMBAYARAN UKT (UANG KULIAH TUNGGAL) DAN KESANGGUPAN MENYELESAIKAN PEMBAYARAN TERHADAP STUDI SAMPAI LULUS STRATA-1 MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS PGRI WIRANEGARA - Kurniawan, Dewi Rachmawati; Pradikto, Sugeng (Cahaya Ilmu Bangsa, 2025)
This study aims to examine the influence of the UKT Payment System and the ability to complete payments on studies until graduation of Bachelor's Degree of Economics Education Students at Universitas PGRI Wiranegara. This study uses a quantitative method with an associative approach. The population of the study was all Economics Education students at Universitas PGRI Wiranegara who had completed their Bachelor's degree. The research sample was taken using a purposive sampling technique of 139 students. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results of the study indicate that the UKT Payment System and the ability to complete payments have a significant influence on studies until graduation of Bachelor's Degree of Economics Education Students at Universitas PGRI Wiranegara. A transparent and fair UKT Payment System and the ability to complete payments on time can motivate students to complete their studies. This study provides recommendations for Universitas PGRI Wiranegara to improve transparency and fairness in the UKT payment system, as well as provide assistance and mentoring programs for students who have difficulty in completing UKT payments. Penelitian ini bertujuan untuk mengkaji pengaruh Sistem Pembayaran UKT dan kesanggupan menyelesaikan pembayaran terhadap studi sampai lulus Strata-1 Mahasiswa Pendidikan Ekonomi Universitas PGRI Wiranegara. Penelitian ini menggunakan metode kuantitatif dengan pendekatan asosiatif. Populasi penelitian adalah seluruh mahasiswa Pendidikan Ekonomi Universitas PGRI Wiranegara yang telah menyelesaikan studi Strata-1. Sampel penelitian diambil dengan teknik purposive sampling sebanyak 139 mahasiswa. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa Sistem Pembayaran UKT dan kesanggupan menyelesaikan pembayaran memiliki pengaruh signifikan terhadap studi sampai lulus Strata-1 Mahasiswa Pendidikan Ekonomi Universitas PGRI Wiranegara. Sistem Pembayaran UKT yang transparan dan adil serta kesanggupan menyelesaikan pembayaran tepat waktu dapat memotivasi mahasiswa untuk menyelesaikan studinya. Penelitian ini memberikan rekomendasi bagi Universitas PGRI Wiranegara untuk meningkatkan transparansi dan keadilan dalam sistem pembayaran UKT, serta memberikan program bantuan dan pendampingan bagi mahasiswa yang mengalami kesulitan dalam menyelesaikan pembayaran UKT.